Evaluation of Immunochromatography Test Using Tp17 Antigen for Detection of Treponemal Antibody in Blood Donors - Dwi Rahayuningsih; Aryati Aryati; Budi Arifah (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2019)
Syphilis transmission through blood transfusion urged WHO recommend examination of treponemal antibody in blood donors. Treponemal antibody was identified to be formed against the membrane of lipoprotein antigen Tp15, Tp17, and Tp47 of T.pallidum. Tp17 antigen may have important role in the pathogenesis of syphilis. Evaluation of CLIA method using Tp17 antigen showed a good diagnostic value. Currently immunochromatography test using Tp17 antigen was available but the diagnostic value has not been widely published. The aim of this study was to determine the diagnostic value of immunochromatography test using Tp17 antigen for treponemal antibody detection in blood donors. Total 100 serum samples with reactive (n=66) and non-reactive (n=34) treponemal antibody screened with ELISA and CLIA methods in blood transfusion unit of Surabaya, Mojokerto, and Sidoarjo Indonesian Red Cross from May 2018-August 2018 were examined for treponemal antibody with immunochromatography test using Tp17 antigen (StandardTM Q Syphilis Ab, Standard Biosensor) and Fluorescent Treponemal Antibody Absorption /FTA-ABS (EUROIMMUN, AG) as gold standard. Kappa Cohen analysis showed the concordance of immunochromatography test using Tp17 antigen was moderate and significant with IgG anti-treponemal FTA-ABS (k = 0.477 p: 0.000). The IgM anti-treponemal was non-reactive in all samples. The sensitivity was 69.8% with 81% of specificity. The sensitivity was not high may be due to the use of a single antigen (Tp17) while the treponemal antibody was formed by Tp15, Tp17, and Tp47 antigen predominantly, the others possbilities were decreased of IgG anti-Tp17 in donors after syphilis treatment, and differences of gold standard with other studies (FTA-ABS vs TPHA). Further study was needed with TPHA that was routinely used as a confirmation test, Western Blot to determine the antibody others than anti-Tp17, and non-treponemal test to determine the disease activity.